Diversity of arterial cell and phenotypic heterogeneity induced by high-fat and high-cholesterol diet - Wen, Jieqi; Ling, Rongsong; Chen, Ruiyue; Zhang, Siyan; Dai, Yarong; Zhang, Tingtao; Guo, Fanyu; Wang, Qingxin; Wang, Guixin; Jiang, Yizhou (Frontiers in Cell and Developmental Biology, 2023)
Lipid metabolism disorder is the basis of atherosclerotic lesions, in which cholesterol and low-density lipoprotein (LDL) is the main factor involved with the atherosclerotic development. A high-fat and high-cholesterol diet can lead to this disorder in the human body, thus accelerating the process of disease. The development of single-cell RNA sequencing in recent years has opened the possibility to unbiasedly map cellular heterogeneity with high throughput and high resolution; alterations mediated by a high-fat and high-cholesterol diet at the single-cell transcriptomic level can be explored with this mean afterward. We assessed the aortic arch of 16-week old Apoe−/− mice of two control groups (12 weeks of chow diet) and two HFD groups (12 weeks of high fat, high cholesterol diet) to process single-cell suspension and use single-cell RNA sequencing to anatomize the transcripts of 5,416 cells from the control group and 2,739 from the HFD group. Through unsupervised clustering, 14 cell types were divided and defined. Among these cells, the cellular heterogeneity exhibited in endothelial cells and immune cells is the most prominent. Subsequent screening delineated ten endothelial cell subsets with various function based on gene expression profiling. The distribution of endothelial cells and immune cells differs significantly between the control group versus the HFD one. The existence of pathways that inhibit atherosclerosis was found in both dysfunctional endothelial cells and foam cells. Our data provide a comprehensive transcriptional landscape of aortic arch cells and unravel the cellular heterogeneity brought by a high-fat and high-cholesterol diet. All these findings open new perspectives at the transcriptomic level to studying the pathology of atherosclerosis.